Assessment of Self-Medication Pattern in Elderly (Indian Journal of Public Health Research & Development, 2020)
Objective: To analyze the prevalence and pattern of self-medication and the various socio-demographicfactors that influence self-medication in elderly patients and also assess the impact of education interventionon self-medication knowledge, attitude in elderly patients. Methodology: A community based cross sectionalstudy was conducted on Bangalore area such as Bellandur, Carmelaram, Kaikondrahalli and Naganahalliover the period of 6months in 320 subjects. The demographic, clinical and social data were collected intospecially designed case report form. The assessment of self-medication was carried out using modifiedstructured questionnaire11 on the day zero and 30. The patient education intervention was carried out on theday zero. The patient education intervention about self-medication was carried out verbally as well as byproviding patient education information leaflets. Whenever they practiced self-medication they were askedto mark in the calendar and the data was analyzed. Results: The data on assessment of self-medicationin elderly were collected from 320 study participants, a significant correlation was observed for elderlyaged above 65 years aged above. Moderate correlation for economic status, education and occupation werefound. Significant correlation was observed with medical history of the patient. Fever 66.25%, headache54.68%, cough and cold 38.43%, were the most common illness where self-medication being used. Antipyretic 58.5%, anti- histamine 34.68%, anti-diabetic 19.68% were most commonly used self-medicatingdrugs. Pharmacist 79.30%, self-decision 30.93% and care takers 25% were the most common source forinformation about self-medication. Time saving 68.75%, no need to visit doctor for minor illness61.25%, previous use of medication 55.93% and economic 53.43% were the major reason for self-medication.Conclusion: The results indicate that self-medication is widespread among elderly and 100% of elderly fromthe study population practiced self-medication without consulting the physician. The various factors likereason, indication and source associated with self-medication were analyzed during the study. A significantassociation between knowledge and attitude among the study population was drawn from the pre and poststudies. The intervention will require better patient education of the public and health professionals to avoidthe irrational use of drugs.
Keywords: Self-medication, KA, Community, Allopathic drugs, OTC, Elderly